2017
DOI: 10.1002/ana.24886
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of antiepileptic drug efficacy in childhood absence epilepsy

Abstract: Objective Determine if common polymorphisms in CACNA1G, CACNA1H, CACNA1I, and ABCB1 are associated with differential short term seizure outcome in Childhood Absence Epilepsy (CAE). Methods 446CAEchildren in a randomized double blind trial of ethosuximide, lamotrigine and valproate had short term seizure outcome determined. Associations between polymorphisms (minor allele frequency ≥15%)in four genes andseizure outcomes were assessed. In vitro electrophysiology on transfected CACNA1H channels determined impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 36 publications
(91 reference statements)
2
48
0
1
Order By: Relevance
“…ETX is presumed to have its major therapeutic effect by reducing low threshold T‐type calcium channel currents in the thalamus . A pharmacogenetic study of ETX efficacy in CAE identified 2 polymorphisms of the T‐type calcium channel (CACNA1H rs61734410/P640L, CACNA1I rs3747178) that were more common in patients who were not seizure‐free, and in vitro studies showed that ETX's rate of calcium current decay was reduced for the P640L polymorphism seen in treatment nonresponders, compared to the wild‐type channel . The link between these genetic findings and the pretreatment ictal network that we have identified in this study is unclear; however, we speculate that if a child has a network driven by the frontal cortex, where ETX may not work as effectively as in the thalamus, then this may provide a mechanistic explanation for their poor response to the treatment (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ETX is presumed to have its major therapeutic effect by reducing low threshold T‐type calcium channel currents in the thalamus . A pharmacogenetic study of ETX efficacy in CAE identified 2 polymorphisms of the T‐type calcium channel (CACNA1H rs61734410/P640L, CACNA1I rs3747178) that were more common in patients who were not seizure‐free, and in vitro studies showed that ETX's rate of calcium current decay was reduced for the P640L polymorphism seen in treatment nonresponders, compared to the wild‐type channel . The link between these genetic findings and the pretreatment ictal network that we have identified in this study is unclear; however, we speculate that if a child has a network driven by the frontal cortex, where ETX may not work as effectively as in the thalamus, then this may provide a mechanistic explanation for their poor response to the treatment (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic groups of patients with CAE have been proposed based on differences in their pretreatment seizure semiology, electroencephalography (EEG), presence of attention deficits, and treatment response . Clinical outcome is clearly variable, with 19.5% of patients failing to respond to the first‐line treatment, ethosuximide (ETX) . This individual variability also extends to the brain networks responsible for absence seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography shows generalized 2.5‐3.5 Hz spike‐and‐wave discharges. Susceptible CAE genes, such as CACNA1H , a Ca v 3.2 T‐type calcium channel gene, are primarily associated with ion channels . CAE is also related to nonion channel genes, such as NIPA2 , a highly selective magnesium transporter gene …”
Section: Introductionmentioning
confidence: 99%
“…channel gene, are primarily associated with ion channels. 5 CAE is also related to nonion channel genes, such as NIPA2, a highly selective magnesium transporter gene. 6 NIPA2 encodes nonimprinted Prader-Willi/Angelman syndrome region protein 2.…”
mentioning
confidence: 99%
“…As a means of targeted treatment and personalized medicine, pharmacogenetics has currently drawn a lot of attention in many neurologic and psychiatric diseases (36)(37)(38)(39)(40). Although many studies have focused on the contribution of genetic factors in autism (41,42), their role as therapeutic elements stays illusive.…”
Section: Discussionmentioning
confidence: 99%